Sociología de la ciencia y cienciometría: una revisión de las teorías subyacentes (2013)
ABSTRACT: This article presents a review of main sociological theories that underlie to scientometric articles that aim to present study cases. This review presents three fundamental models categorized as: Functionalists Scientometric Models, Translation Scientometric Models and Systemic Scientometric Models. Theoretical and methodological principles are explained. At the end a contrasts is made.